The Effect of Motivation and Compensation on the Job Satisfaction of Online Gojek Drivers in Palembang City - Denty Natali; Clara Gloria Koraag; Johan Gunady Ony (AKSIOMA : Jurnal Manajemen, 2026)
Ride-hailing services in Palembang play an important role in community mobility; however, drivers’ job satisfaction remains an issue. Previous studies have shown inconsistent results regarding the influence of motivation and compensation on job satisfaction, indicating a research gap in digital platform-based work. This study aims to analyze the effect of motivation and compensation on the job satisfaction of ride-hailing drivers. A quantitative approach was employed with a sample of 101 respondents, determined using the Lemeshow formula and convenience sampling. Data were analyzed using multiple linear regression. The results show that motivation and compensation have a positive and significant effect on job satisfaction, contributing 72.9% of the variance. The novelty of this study lies in testing the model within a nonconventional, flexible work context. Theoretically, this study reinforces motivation and compensation theories in the digital economy and provides empirical contributions to human resource management research.